P–647 How do migraine attacks change during puberty?. (6th August 2021) - Boettcher, B; Kyprianou, A; Wildt, L; Lechner, C; Kößler, M; Neururer, S; Bettina, T; Matthias, B; Rostasy, K; Rauchenzauner, M
Abstract: Study question: How do the stage of puberty and the menstrual cycle influence characteristics of migraine? Summary answer: During puberty, the frequency of migraine attacks increases, especially during the follicular phase. The pattern of migraine changes to a typical adult pattern of migraine. What is known already: Up to puberty, headaches are as common in girls as in boys. After the onset of puberty migraine is more prevalent in adolescent girls suggesting an association with sex hormones. Attacks of menstrual migraine are characterized by a longer duration, tend to be more severe, and are less responsive to acute medication compared to migraine attacks which are independent from the menstrual cycle phase. Study design, size, duration: For this prospective cohort study 47 girls were recruited from two Departments of Pediatrics and Adolescent Medicine between 01/2016 and 12/2018. Participants/materials, setting, methods: Girls between 7 and 18 years old, diagnosed with migraine without aura according to the "International Classification of Headache Disorders II" diagnostic criteria, took part. Three groups (pre-, peri-, and postpubertal) were formed according to the Tanner stage and the onset of a regular menstruation. Girls kept a daily headache and menstrual cycle diary over 8 weeks. Ovulatory cycles were analyzed by weekly progesterone saliva tests. Main results and the role of chance: Three groups according to Tanner stage and onset of regular menstruation were compared: pre- (n = 16), peri- (n = 19) and post-pubertal (n = 12) girls. A significant difference in migraine frequency was found between pre- and post- pubertal girls (p = 0.005). Headache characteristics did not differ significantly between the three groups. Interestingly, a higher frequency of attacks in follicular phase occurred compared to luteal phase (p = 0.030). Limitations, reasons for caution: Repeated blood sampling would have been a more reliable technique compared to saliva assays. The sample size is small. Wider implications of the findings: During puberty, the number of migraine attacks but not the specific headache characteristics changes in adolescent girls which should be taken into consideration regarding the management of these patients. Trial registration number: AN2013–0027